Junk Food And Dental Caries In School Children - A. ZULFIQAR, P. NAEEM S, IDREES H. SALEEMI, M. A. SAGHIR (Journal of Fatima Jinnah Medical University, 2018)
Objective: To estimate the cases of dental carries in school children and to document association of dental carries with consumption of junk food. Design: Case control study. Place and Duration of Study: The study was conducted at Young Women Christian Association (YWCA) School at Fatima Jinnah Road, Lahore, from 1st May 2010 to 31st May 2010. Patients and Methods: All the students (n=162) from class 1 to 10 were clinically examined as part of annual general physical examination for which informed consent was taken from parents. Dental oral hygiene; particularly dental caries was looked for. Children with caries were taken as cases and children without caries were controls. Every child was asked about the type of lunch they eat at school; lunch from home or food from school canteen; food from the canteen was taken as proxy for junk food consumption. Results: There were 100 males and 62 females. Average age was 9 years (range 4-17 years). 120 (74%) children ate junk food. 73 (45%) children had dental caries; 64 (88%) ate junk food while 9 (12%) ate food brought from home. Hence there were 73 cases and 89 matched controls within the same group. The children who consumed junk food, were four times more, likely to have dental carries with an Odd ratio of 4.19 (confidence interval of 1.84-9.1) and p-.value of 0.000. Conclusion: Dental caries is a common problem in school going children. The children consuming junk food are four times more prone to develop dental caries.